Removal of selected chlorinated phenolic compounds from water sources in Vaal Triangle using HPLC, Macadamia nutshell activated carbon and solid phase extraction - Machedi, Sechaba (My University, 2017)
In this study, analytical method for determining the chlorinated phenols in water was developed using High Performance Liquid Chromatography. The following four compounds which are 2, 4, 6- Trichlorophenol (2, 4, 6 TCP), 3-chlorophenol (3CP), 2, 4- Dichlorophenol (2, 4 DCP) and 4-chloro-3-methylphenol (4C3MP) were identified and quantified with a High Performance Liquid Chromatography (HPLC). The validation parameters tested were,: linearity, trueness, precision, detection limit of quantitation, sensitivity, specificity, selectivity. The linear calibration ranges of five standard solution from 1-10 ppm. The linearity ranges between 0.9298-0.9813. The activated carbon based on the waste macadamia nutshell activated carbon (MAC) was investigated for its potential uses as an adsorbent for chlorinated phenols removal and compared with grafted macadamia nutshell activated carbon (GMAC). The adsorbent was characterized with Fourier transform infrared spectrophotometer (FTIR), scanning electron microscope (SEM) and thermo gravimetric analysis (TGA). The parameters such as pH, temperature, contact time, concentration and adsorbent were investigated by adsorption technique. The strata C18E has been used before for the same reason and therefore the research was based on mimic the functional group of solid phase extraction (SPE) into macadamia activated carbon (MAC). The functional groups in SPE C18E are benzene and octadecyl. MAC was grafted with strata C18E functional groups to compare its potential with the SPE. The pseudo-first-order and pseudo-second-order kinetic models were applied to verify the experimental data. The pseudo-second order exhibited the best fit for the kinetic studies for MAC adsorption. Chemical removal of chlorinated phenols from wastewater is necessary to reduce harmful products on the environment and human health. Chlorinated phenols have been previously listed as some of the highest priority contaminants and as well as mainly important capability carcinogenic toxins released from chemical plants. Their availability in water supplies was perceived by their bad taste and smell. The acceptable chlorinated phenols concentration in portable water is 1 (mg/l) base on the approval of world health organization. The permanent checking of chlorinated phenols in environmental samples has a greater significance and stresses highly effectiveness, common selectively and great sensitively methods. The maximum uptake of Phenol using weighed mass of MAC was found to be 78 % and for GMAC was 84% for both 2,4,6TCP. t=250 min, pH=5, Co=1mg/l, T = 25 oC and m = 0.3 g/l were the optimum condition for Phenol-MAC system and GMAC system. Over all analysis of equilibrium model analysis indicates the fitness of Langmuir isotherm model to Phenol MAC adsorption system, suggesting a monolayer adsorption of phenol on the surface of MAC. Phenol adsorption capacity of MAC was found to be decreasing with increase in temperature suggesting that the adsorption process was exothermic in nature, which was further supported by the negative values of change in enthalpy. Characterization of MAC and GMAC confirmed the mesoporous texture, highly carbonaceous nature and a higher effective surface area of 912 m2/g. The highest phenol uptake capacity of GMAC was found to be 8.0049 mg/g. The optimal conditions for various process parameters are t = 250 min, pH=5, Co=1mg/l, T = 25 oC and m = 0.3 g/l were the optimum condition for Phenol-GMAC system. Like Phenol-MAC system, the kinetics studies confirmed that Phenol-GMAC adsorption system can be described by pseudo- second-order kinetics model. Equilibrium model analysis indicates the fitness of Langmuir isotherm model to Phenol-MAC adsorption system, suggesting a monolayer adsorption of phenol on the surface of GMAC. Phenol adsorption capacity of GMAC was found to be decreasing with increase in temperature suggesting that the adsorption process was exothermic in nature, which was further supported by the negative values of change in enthalpy. The negative values of Gibb’s free energy suggested that adsorption of phenol onto GMAC was a spontaneous process.
M. Tech (Department of Chemistry, Faculty of Applied and Computer Sciences) Vaal University of Technology.
Keywords: Trichlorophenol, High Performance Liquid Chromatography (HPLC), thermo gravimetric analysis (TGA).; High performance liquid chromatography.; Macadamia nut.; Phenols.